THE EFFECT OF FAMILY LIFE EDUCATION PROGRAM ON PARENTS' ATTITUDES TOWARDS GENDER ROLES WITH SHARING DOMESTIC ROLES AND RESPONSIBILITIES (Third Sector Social Economic Review, 2024)
The aim of this study is raise awareness in parents with children aged 0-6 years regarding their gender-related problems, increase their knowledge level to cope with problems and create a change of attitudes and behaviors. In the study, “Pretest-Posttest Control Group Design” was used. The research was conducted with a total of 32 parents, 16 parents in the experimental group and 16 parents in the control group. “The Family Life Education Program was given to the experimental group in 7 sessions of 90 minutes, once a week. Effectiveness of the experimental procedure was tested via two-factor ANOVA test. As a result of the study, it was found that the effect of the Family Life Education Program developed within the scope of the study differed depending on the gender of the parents in the experimental group. It was determined that the average scores of the fathers after the training on the ASGRP and the sub-dimensions of the scale related to ""Traditional"" and ""Egalitarian"" attitudes were high. In addition, there was an increase in the average scores they received from DRSPS and the ""Traditional Role and Responsibility Sharing"" and ""Egalitarian Role and Responsibility Sharing"" sub-dimensions of the scale. This result shows that the develop education program had an impact on fathers' attitudes towards gender roles and sharing of domestic responsibilities, and that they adopted a more egalitarian and participatory approach compared to before the training.
Keywords: Family life cycle; families with children aged 0-6 years; gender roles; family life education; sharing roles and responsibilities within the family